Patterns of myelinated nerve fibers loss in transthyretin amyloid polyneuropathy and mimics. Issue 7 (4th June 2022) - Du, Kang; Chu, Xujun; Tang, Yuwei; Zhao, Xutong; Yu, Meng; Zheng, Yiming; Deng, Jianwen; Lv, He; Zhang, Wei; Wang, Zhaoxia; Yuan, Yun; Meng, Lingchao
Abstract: Objective: The present study was intended to analyze the characteristics of myelinated nerve fibers density (MFD) of transthyretin amyloid polyneuropathy (ATTR‐PN) and other similar neuropathies. Methods: A total of 41 patients with ATTR‐PN, 58 patients of other common peripheral neuropathies, and 17 age‐and gender‐matched controls who visited the First Hospital of Peking University and performed sural nerve biopsy between June 2007 and August 2021 were included for analysis of MFD. Results: Except the vasculitic neuropathy group, the total and small MFD of patients in the ATTR‐PN group were significantly lower than those of other disease groups. There was an obvious negative correlation between the total MFD and the disease course in the ATTR‐PN group. The disease course of early‐onset and late‐onset symptoms was similar, but the loss of large myelinated nerve fibers (MF) was more severe for the latter. In addition, all late‐onset and most early‐onset patients had severely reduced MFD after a 2 years' disease course. The MFD in ATTR‐PN patients was negatively correlated with Neuropathy Impairment Score (NIS) and Norfolk Quality of life‐diabetic neuropathy (Norfolk QOL‐DN) score. Conclusion: MF is lost differently in ATTR‐PN and in other common peripheral neuropathies. The late‐onset and early‐onset ATTR‐PN patients have different patterns of loss of large and small MF.